(untitled) (INMR - Innovation & Management Review, 2023)
Purpose – The purpose of this article is to investigate the interrelationships between innovation climate and humancapital in the development of dynamic capabilities related to innovation. The study presents a set of concepts aboutvariables involved in the innovation process and their interrelationship, addressing the analysis of internationalscientific production related to the antecedents of the innovation climate, human capital and dynamic capabilities.Design/methodology/approach – A review of the literature from 1998 to 2018 was carried out, usingdescriptive statistical methods, at first, and qualitative analysis of the results in order to visualize the currentconfiguration of the field of study of innovation background.Findings – The results demonstrate a significant number of studies relating human capital and dynamiccapabilities and little quantitative significance in studies relating to a climate of innovation and dynamiccapabilities. The research describes how the dynamic capabilities of innovation have been approached in aconceptual model based on the perspective of human capital and innovation climate.Research limitations/implications – The study did not contemplate the analysis of the interrelationshipbetween the resource configuration construct and the dynamic innovation capacities (part of the gap pointed out byTuzovic, Wirtz and Heracleous (2018), constituting a perceptible limitation of the analyzes carried out in this article.Practical implications – The influence of the innovation climate construct and its relationship with dynamicinnovation capabilities deserves greater attention in research with an empirical approach, constituting a field tobe explored by scientific research in organizations.Originality/value – The research sought to investigate the gap involving the interrelations betweeninnovation climate and human capital in the development of dynamic capabilities related to innovation,indicating the need for further empirical studies on the subject.